The role of sociology in leadership in the church (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The strong relationship between society and the Church is explained in sociology or sociological theory. We know that society is a group of individuals who give rise to social groups and institutions named the Church. So, we need to look at the bond between the community and the Church, in this case, the church leadership, which is very closely related to the processes and factors of social interaction. In this journal, it is hoped that a common thread can be found that the role of sociology is decisive in church practice in this context of Leadership in the Church.